2017
DOI: 10.1186/s12931-017-0591-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific lung functional changes in adult mice exposed only to second-hand smoke in utero

Abstract: BackgroundAn increasing number of epidemiological and experimental studies have associated exposure to second-hand smoke (SHS) during pregnancy with adverse outcomes in newborns. As we have previously shown in mice, in utero exposure to SHS at critical stages of fetal development, results in altered lung responses and increased disease susceptibility upon re-exposure to irritants (SHS or ovalbumin) in adulthood. In this study, we asked whether the in utero SHS exposure alone is sufficient to alter lung structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 81 publications
5
39
1
Order By: Relevance
“…In HRS, men exposed to passive smoke had a higher risk of heart disease and stroke than women. In a mouse model of prenatal exposure to passive smoke, males had greater alteration in adult lung tidal volume [35].…”
Section: Plos Onementioning
confidence: 94%
See 1 more Smart Citation
“…In HRS, men exposed to passive smoke had a higher risk of heart disease and stroke than women. In a mouse model of prenatal exposure to passive smoke, males had greater alteration in adult lung tidal volume [35].…”
Section: Plos Onementioning
confidence: 94%
“…Further studies of sex differences in response to cigarette smoke should consider physiologically distinct stages of the lifespan: development (0-18), young adulthood (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), middleage including post-menopause , and older ages when chronic diseases increase exponentially (60+). For example, a mouse model of air pollution toxicity had attenuated responses of lung and brain by middle-age (18 months) [46,47].…”
Section: Plos Onementioning
confidence: 99%
“…The observed pulmonary morphological changes could further indicate a higher susceptibility for COPD . This contention is supported by a study showing that in utero ETS exposure alone can be sufficient to induce lung structural changes …”
Section: Models Of Sidestream Cigarette Smoke Exposure During Pregnancymentioning
confidence: 60%
“…Nicotine-induced alterations in alveolar size and abnormal lung function were most prominent in males. This is intriguing considering previous evidence of greater deleterious effects of nicotine or second-hand smoke on lung function in males (135,168). Other studies have shown similar differences in lung function, but did not examine the role of sex within their groups (114).…”
Section: Discussionmentioning
confidence: 84%
“…This suggests that the weight loss due to infection was not the factor driving lung functional abnormalities. Lastly, publications have shown that in animal models, males have been highly implicated to have decreased lung function compared to females, but only when an extrinsic factor (such as nicotine or smoke exposure) is involved (135,168,(241)(242)(243).…”
Section: Pulmonary Function Testingmentioning
confidence: 99%